Shared leadership in sport for development and peace: A conceptual framework of antecedents and outcomes - Kang, Seungmin; Svensson, Per G. (Sport management review, 2019)
•The concept of shared leadership and its applicability in SDP is examined.•A collective view of leadership is valuable for the distinct nature of SDP.•Nine propositions are presented regarding antecedents and outcomes.•Addresses gap in literature on leadership in SDP.•Future directions for research on shared leadership in SDP are discussed. A broad range of organizations are involved in the field of Sport for Development and Peace (SDP). The complex environmental factors and internal capacity challenges surrounding SDP organizations put additional pressures on SDP managers who are required to balance multiple organizational demands to achieve sustainable program outcomes. Although scholars have begun to explore managerial aspects of SDP efforts, literature on the nature of leadership in SDP remains scarce. In this article, therefore, the authors introduce the concept of shared leadership and arguments for why considering leadership as a collective phenomenon is of particular value in SDP. Specifically, a conceptual framework is developed to identify antecedents and outcomes of shared leadership in SDP. Nine propositions are presented along with a discussion of future areas of study regarding shared leadership in efforts to use sport as a means for achieving development and peace-building outcomes. Limitations of this leadership perspective are also outlined.